2020
DOI: 10.1097/ico.0000000000002321
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Limbal Epithelial Transplantation Modified With Solid Platelet-Rich Plasma for Bilateral Limbal Stem Cell Deficiency

Abstract: Purpose: To present successful management of bilateral limbal stem cell deficiency (LSCD) by using an allogeneic limbal epithelial stem cell transplantation together with solid activated platelet-rich plasma (PRP). Methods: A 59-year-old man with a history of bilateral LSCD due to penicillin-induced Stevens–Johnson Syndrome suffered from a lime corneal burn in his right eye, leading to a total LSCD with severely reduced visual acuity. After stabilizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…37 There is a recently published single case report by Alvarado et al where in they have used solid PRP along with Allogenic Limbal stem cell transplant for a patient with previously diagnosed Limbal stem cell deficiency suffering a lime burn and have shown excellent improvement in BCVA postoperatively. 38…”
Section: Peri-ocular Chemical and Thermal Burnsmentioning
confidence: 99%
“…37 There is a recently published single case report by Alvarado et al where in they have used solid PRP along with Allogenic Limbal stem cell transplant for a patient with previously diagnosed Limbal stem cell deficiency suffering a lime burn and have shown excellent improvement in BCVA postoperatively. 38…”
Section: Peri-ocular Chemical and Thermal Burnsmentioning
confidence: 99%
“…Healthy reepithelization and visual improvement were successfully achieved. 37 We found epithelial stem cell markers (ABCG2 and P63) over the ocular surface of corneal buttons obtained from our patients. These corneal surface progenitor cells play a supportive role in the continued regeneration of epithelial cells over the cornea.…”
Section: Discussionmentioning
confidence: 52%
“…As far as we can ascertain, this is the first intraindividual contralateral randomized study to assess corneal epithelial healing after instillation of PRP solutions in patients undergoing PTK. Until now, topical PRP treatment has been reported to be effective for the treatment of several ocular surface disorders, such as symptomatic dry eye [ 3 5 ], ocular surface syndrome after laser in situ keratomileusis (LASIK) [ 6 8 ], persistent corneal epithelial defect [ 9 12 ], recurrent corneal erosion [ 13 ], dormant corneal ulcers [ 14 17 ], acute hydrops for keratoconus [ 18 ], and limbal stem cell deficiency [ 19 ]. Although there have so far been several studies on the effect of topical PRP solutions on corneal epithelial healing, this intraindividual study indicated that the PRP was safe and effective for promoting corneal epithelial recovery and that it reduced subjective symptoms and increased patient satisfaction, in post-PTK patients.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet-rich plasma (PRP) has been shown to promote wound-healing responses of biological tissues in a variety of medical fields [ 1 , 2 ]. In the field of ophthalmology, topical PRP treatment has been used for the treatment of various corneal diseases, such as symptomatic dry eye [ 3 5 ], ocular surface syndrome after laser in situ keratomileusis (LASIK) [ 6 8 ], persistent corneal epithelial defect [ 9 12 ], recurrent corneal erosion [ 13 ], dormant corneal ulcers [ 14 17 ], acute hydrops for keratoconus [ 18 ], and limbal stem cell deficiency [ 19 ]. These results suggest that PRP is effective for the treatment of such intractable diseases, because it promotes corneal epithelial healing responses, possibly resulting from the release of various growth factors.…”
Section: Introductionmentioning
confidence: 99%